STUDI TENTANG MISKONSEPSI SISWA DAN MAHASISWA TERHADAP KONSEP RANGKAIAN LISTRIK ARUS SEARAH (DIRECT CURRENT) - Hartanto, Theo Jhoni; Nawir, Muhammad (Vidya Karya, 2017)
Abstract. The purpose of this study is to describe the understanding of the direct current electric circuit basic concept that posses by senior high school students and natural science (physics) student teacher. The research instrument used in this study was the concept understanding test in the form of objective test that accompanied by certainty of response index (CRI). This test was developed from some relevant studies. The concept understanding test was given to 30 senior high school students and also 32 graduate students of physics education study program in Palangka Raya City. From the study result, it was found that the same of the kind of missconception problem tends to be found among the senior high school students and also the graduate students, for example is the concept of the consumption model of electric current and battery are the fixed current supply. The missconceptions on the direct current circuit that found in this study were also have been founded in some studies from other countries for various group of age and level of study. Keywords: missconception, electric circuit, direct current, CRI. Abstrak. Tujuan dari studi ini adalah untuk memberikan gambaran mengenai pemahaman siswa di sekolah menengah (SMA) dan mahasiswa calon guru IPA (fisika) terhadap konsep dasar rangkaian listrik arus searah. Instrumen penelitian yang digunakan dalam penelitian ini berupa tes pemahaman konsep dengan pilihan ganda beralasan terbuka disertai dengan certainty of response index (CRI). Tes ini dikembangkan dari beberapa studi yang relevan. Tes pemahaman konsep diberikan kepada 30 siswa SMA dan 32 mahasiswa Prodi S1 Pendidikan Fisika yang berada di Kota Palangka Raya. Berdasarkan hasil studi ditemukan kesalahan konsep (miskonsepsi) yang cenderung sama pada siswa dan mahasiswa, antara lain model konsumsi arus listrik dan baterai merupakan sumber arus listrik yang tetap. Kesalahan konsep (miskonsepsi) mengenai rangkaian listrik arus searah yang ditemukan dalam studi ini juga ditemukan di beberapa studi di luar negeri pada berbagai kelompok umur dan jenjang pendidikan. Kata kunci: miskonsepsi, rangkaian listrik, arus searah, CRI